Seriously struck roofs (Bulletin KNOB, 2007)
As ‘lids’ on monuments, timber roofs are particularly sensitive to what took place in the surroundings of or within the building itself. Calamities such as collapse, town fires, explosions, war, bolts of lightning and storms can be visible in the woodwork.We have followed such effects in three towns: Leiden where the church tower collapsed in 1512. Zwolle where the tall spire of St Michael's church was struck by lighting as often as three times, as the church roofs show, and Roermond where we used church buildings as parameters for establishing the scale of a town fire in 1665 of which a painted street plan was also made.In some cases the reconstruction was recognizably contemporary, in others - as in Utrecht after the hurricane of 1674 - usable old timber was rearranged, whereby the newly applied gently pitched roof catches the eye, and in yet other cases the aim appears to have been to copy the medieval construction as accurately as possible.The latter occurred in the Buitenkerk in Kampen after the collapse of the tower in 1607 and in the reconstruction of a medieval tunnel vault in a former chapel, the later lecture hall of the University of Leiden where in 1616 a fire broke out. Small, subtle phenomena, such as the use of pinewood or the use of cut assembly marks show that it concerns a copy of the Middle Ages.In other situations we gratefully took advantage of dendrochronological datings presenting fixed points of departure in time. What gave rise to all this is the explosion of a ship with gunpowder in Leiden on 12 January 1807, which is to be commemorated by the KNOB in a symposium on the same date, 200 years later. The other articles in this issue deal with different architecture in Leiden, because the calamity is commemorated separately in a book and an exhibition.